POTENSI SUMBER DAYA ARKEOLOGI BAWAH AIR DI KALIMANTAN - Ida Bagus Putu Prajna Yogi (Balai Arkeologi Kalimantan Selatan, 2010)
Many shipwrecks have been found in the Indonesian waters loaded with ceramics, ship components and others. There are at the least 463 shipwrecks loaded with invaluable artefacts; however, such number is too small compared to the vastness of the Indonesian waters and the maritime history in regard to Indonesian Archipelago. One of islands which provide data on shipwreck is Kalimantan; it lies practically in the centre of the Indonesian Archipelago and has the longest beach and large rivers that cuts into the interior of the island and functions as the artery of water transfortation in the past. The suggest prospective archaeological data to be unearhed. Unfortunately, up until today, little underwater archaeological research has been carried out in Kalimantan. This article discusses the importance of carrying out underwater archaeological research in Kalimantan waters.